Analysis of quality control in clothing production using SQC (Statistical Quality Control) and 5W+1H methods - Nugroho, Iwan Satriyo; Maulana, Ade Alam; Mubharoq, Muhamad Rizqi; Rafi, Mochamad; Fuadi, Nazibul; Alam , Saepul (ARKA INSTITUTE, 2024)
CV Tujuh Pusaka Tala is a start-up company engaged in the clothing and sports jersey convection industry, as well as marching band musical instruments known by the brands 7MJR Store for clothing and SevenMajor for marching band musical instruments. This study was conducted to analyze the quality control of clothing production at CV. Tujuh Pusaka Tala using the Statistical Quality Control (SQC) method and the 5W and 1H approach to minimize defective products. The SQC methods used include Checksheet, Control Map, Histogram, Pareto Diagram and Cause and Effect Diagram to identify and control variability in the production process. While the 5W and 1H approach is applied to understand the main causes of product defects and find the right solution. The results of the study showed that there were 4 types of defects in the production process at CV. Tujuh Pusaka Tala, namely printing defects, screen printing defects, stitching, and material defects. The main factors causing production defects include humans, materials, machines, methods, and the environment. It can be concluded that the quality control of clothing production at CV. Tujuh Pusaka Tala using the Statistical Quality Control (SQC) method and the 5W and 1H approach to minimize defective products has been implemented well so that it can minimize the existence of defective products.